Characterization of the G protein-coupled receptor family SREB across fish evolution - Timothy S. Breton (Nature Portfolio, 2021)
Abstract The SREB (Super-conserved Receptors Expressed in Brain) family of G protein-coupled receptors is highly conserved across vertebrates and consists of three members: SREB1 (orphan receptor GPR27), SREB2 (GPR85), and SREB3 (GPR173). Ligands for these receptors are largely unknown or only recently identified, and functions for all three are still beginning to be understood, including roles in glucose homeostasis, neurogenesis, and hypothalamic control of reproduction. In addition to the brain, all three are expressed in gonads, but relatively few studies have focused on this, especially in non-mammalian models or in an integrated approach across the entire receptor family. The purpose of this study was to more fully characterize sreb genes in fish, using comparative genomics and gonadal expression analyses in five diverse ray-finned (Actinopterygii) species across evolution. Several unique characteristics were identified in fish, including: (1) a novel, fourth euteleost-specific gene (sreb3b or gpr173b) that likely emerged from a copy of sreb3 in a separate event after the teleost whole genome duplication, (2) sreb3a gene loss in Order Cyprinodontiformes, and (3) expression differences between a gar species and teleosts. Overall, gonadal patterns suggested an important role for all sreb genes in teleost testicular development, while gar were characterized by greater ovarian expression that may reflect similar roles to mammals. The novel sreb3b gene was also characterized by several unique features, including divergent but highly conserved amino acid positions, and elevated brain expression in puffer (Dichotomyctere nigroviridis) that more closely matched sreb2, not sreb3a. These results demonstrate that SREBs may differ among vertebrates in genomic structure and function, and more research is needed to better understand these roles in fish.